2011
DOI: 10.1186/2047-783x-16-11-495
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of heat shock protein27 in the mouse dental pulp after immediate teeth separation

Abstract: AimAfter immediate teeth separation, expression of HSP27 in the mouse dental pulp was examined. Immunohistochemistry was performed to examine the incidence of HSP27 expression.Materials and methodsA total of 36 8-week-old ddY mice were used as experimental subjects and a wedge was inserted in between maxillary right molars. The wedge was removed 30 min or 3 h after insertion. Animals were immediately sacrificed after the removal of wedge or until 1 week later and serial sections from paraffin-embedded tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Heat shock proteins are induced by heat and a variety of other physical, chemical, and biologic stressors such as ischemia, infection, and inflammation [18,19]. They have roles in cell repair and defense mechanisms [20]. Some heath shock proteins such as HSPA5 are also upregulated in many types of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Heat shock proteins are induced by heat and a variety of other physical, chemical, and biologic stressors such as ischemia, infection, and inflammation [18,19]. They have roles in cell repair and defense mechanisms [20]. Some heath shock proteins such as HSPA5 are also upregulated in many types of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ALP expressed in the early stage of calcification associated with odontoblast differentiation is an index of odonoblastic activity [33]. In our previous studies, we induced the differentiation of dental pulp cells by adding injurious stimulation to the periodontium and pulp [10,11]. Nabeyama et al have shown that there is a weak positive reaction for Runx2 in the pulp tissue that has not been artificially stimulated [10].…”
Section: Cell Differentiation Of Bmdcs Recruited To the Dental Pulpmentioning
confidence: 99%
“…Saito et al stimulated the pulp by the same experimental method as Nabeyama et al and examined the expression of HSP27 [11]. The pulp showed a weak positive reaction for HSP27 from the immunohistochemical reaction of the control group.…”
Section: Cell Differentiation Of Bmdcs Recruited To the Dental Pulpmentioning
confidence: 99%
See 2 more Smart Citations